2015
DOI: 10.1007/s11356-015-5789-4
|View full text |Cite
|
Sign up to set email alerts
|

Soil microbial response to tetracycline in two different soils amended with cow manure

Abstract: High amounts of antibiotics are introduced in the soil environment by manure amendment, which is the most important spreading route in soil, with a potential ecotoxicological impact on the environment. The objectives of this study were (a) to assess the tetracycline (Tc) bioavailability in a clay and in a sandy soil, and (b) to evaluate the effects of the Tc and cow manure on the structure and function of soil microbial communities. Clay and sandy soils were spiked with Tc at the concentrations of 100 and 500 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 60 publications
4
27
0
Order By: Relevance
“…Though research frequently focuses on the introduction of pathogenic microbes to the environment from animal manure (Salgado et al 2011), data indicate that manure application is directly associated with increasing numbers of antibiotic-resistant bacteria in soil (Sengeløv et al 2003;Peng et al 2014). Residual antibiotics in land-applied manure exert a selective pressure on resident soil microbes, causing a shift in the microbial community toward more resistant microorganisms (Boxall et al 2003;Pruden et al 2006;Chessa et al 2016). Recent studies show that very low antibiotic concentrations in the environment can induce selection for resistance (Gullberg et al 2011;Liu et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Though research frequently focuses on the introduction of pathogenic microbes to the environment from animal manure (Salgado et al 2011), data indicate that manure application is directly associated with increasing numbers of antibiotic-resistant bacteria in soil (Sengeløv et al 2003;Peng et al 2014). Residual antibiotics in land-applied manure exert a selective pressure on resident soil microbes, causing a shift in the microbial community toward more resistant microorganisms (Boxall et al 2003;Pruden et al 2006;Chessa et al 2016). Recent studies show that very low antibiotic concentrations in the environment can induce selection for resistance (Gullberg et al 2011;Liu et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…More genera showed significant differences in June than in August and October. Therefore, we found that fertilization and vegetation can change some microbial communities in a short period of time (Chessa et al 2016;. Then, a legacy effect can adjust the microbial composition (Elgersma et al 2011).…”
Section: Discussionmentioning
confidence: 91%
“…This could result in an increase in the number of degrading microorganisms and therefore, an increase in enzyme production. Alternatively, the negative effect of XM could have been masked by the increased activity of other microorganisms capable of surviving in the presence of an antibiotic and/or using compounds released from the cells of killed microorganisms [9,64,65]. The effect observed could also be related to the XM degradation in the soil.…”
Section: Discussionmentioning
confidence: 99%